Societal perspective in economic evaluation - A.B, Mohamed Fakhri; Juni, Muhamad Hanafiah; A.M, Rosliza; I., Faisal (Community Health Society Malaysia, 2017)
Background: Before an economic evaluation begins, it is important to specify the study perspective which essentially defines the basis of analysis and determines the relevant cost that need to be accounted for. The aim of this paper is to explore the perspectives in an economic evaluation specifically focusing on societal perspectives, on how it affect costs, its application, as well as its advantages and limitations expected in an economic evaluation. Materials and Methods: Literature search was conducted on Google Scholar and PubMed by using keywords such as perspective of economic evaluation, societal perspective, and economic evaluation. Based on the relevant reports, articles and other publications, details on societal perspective in economic evaluation was summarized in the result and discussion section. Result and Discussion: A model demonstrating societal effects that captured by cost-benefit analysis for cancer patient in New South Wales, Australia was used as an example to see the application of societal perspective, where four different scenarios were discussed on how societal impacts of loss of productivity and income affected the patients, employer and their family members. Among the advantages of incorporating societal perspective in economic evaluation studies is that it may result an optimal resource allocation in decision making and also supports an informed public discussion. However it is also prone to disadvantages, such as it may not always be possible to be included in an economic evaluation in certain setting due to funding or time constraints. Conclusion: Societal perspective is recommended option for public health economic evaluation as it take into account all of the perspectives point of view. Health economic evaluation that were conducted from a narrow perspective and only considered direct costs in the analysis is likely to be biased and could significantly undermine the true benefit of the interventions for society. Furthermore, without societal perspective, it may result in suboptimal resource allocation thus incur losses in the total welfare of society.